The Vivekananda Kendra in India: Its ideological translations and a critique of its social service - Pandya, Samta P. (Critical research on religion, 2014)
This article is based on field work with the Vivekananda Kendra in Kanyakumari, India. The Vivekananda Kendra (“the Kendra”) is a Hindu spiritual organization founded in 1972, based on principles promoted by Swami Vivekananda. The organization’s members translate Vivekananda’s Vedanta and Yoga ideals into national reconstruction. The efforts of Eknath Ranade as the key transmitter of Vivekananda’s ideals, the way he effectively wove austerity, renunciation, and service to realize them, and the Kendra’s strategy of social service and its effects are discussed. In particular, the Kendra’s social service is analyzed on the basis of its social consciousness, its views on social issues and gender, its Hindu nationalist stance, and its relationship with the establishment and the global political economy. This critical discourse highlights the Kendra’s emphasis on Vedantic socialism as opposed to traditional socialism. The lenses by which the Kendra views society are gendered and ethnonationalist. It deals with matters of justice, equity, and state relations from a benevolent patriarchal vantage point.